O dito e o feito nas práticas educativas escolares sobre educação ambiental com crianças - Moraes, Elenice Da Silva (2024)
This dissertation is the result of research linked to the research line: Culture, Educational Processes, and Teacher Training, from the Postgraduate Program in Education of Francisco Beltrão (PPGEFB) at the Western Paraná State University (Unioeste). Its objective is to evaluate what is said and what is done in school educational practices regarding Environmental Education (EE) with children through the bibliographic analysis of scientific productions, mainly dissertations, and theses, on the Brazilian Digital Library of Theses and Dissertations platform (BDTD). It also includes articles from the Brazilian Journal of Environmental Education. The issue addresses education with children, methodological problems related to teaching, and the potential impacts on implementing environmental pedagogical practices. To this end, data concentration and the research corpus were formed by consulting environmental thematic reference platforms. The theoretical framework followed the paths of a critical perspective and approach, with reflections centered on citizen formation context, based on Gadotti (2000) and Guimarães (2004 and 2014), who problematize issues related to the institution and instrumentalization of Environmental Education (EE); Dickmann (2021), who works on the interrelations between ethical-aesthetic-political pedagogical culture present in the totality of school reality; Carvalho (2012), who places EE in a sociocultural context, in historical-social marks, highlighting the importance of educational practices for social transformation; Loureiro (2004, 2006, 2011, 2012, 2013, and 2019) in pedagogical approaches in EE, focusing on historicalsocial-critical aspects; Saviani (1991, 2000, 2005, 2010), emphasizing educational policies in their social function; Dias (2004 and 2006), addressing EE in its socioeconomic, political, and ecological importance aimed at attitudes that contribute to quality of life and solving socio-environmental problems; and Vasquez (1977), addressing social praxis. The results indicate a scarcity of publications on EE with children and highlight the need for the permanent inclusion and intensification of interdisciplinary methodologies on EE from an early age